Bases para a padronização do teste de germinação em três espécies de Solanum L. - Castellani, Estela Dalpim; de Aguiar, Ivor Bergemann [UNESP]; de Paula, Rinaldo César [UNESP] (My University, 2009)
This study aimed to obtain basic information about the seed germination of three species of the Solanum genus (Solanaceae), recommended for restoration of degraded lands: S. granuloso-leprosum, S. lycocarpum and S. pseudoquina. Depending on the species, different seedlots were tested as well as seeds of different densities and colours. The germination tests were performed at constant (25°C) and alternating temperatures (20-30°C), under eight hours photoperiod and with filter paper as substrate. Both total germination percentage and germination speed index were evaluated and the duration of the tests was determined, considering different criteria for germination. The results showed that seeds of S. granuloso-leprosum with low density should be discarded; yellow seeds of S. granuolo-leprosum and green seeds of S. pseudoquina showed higher physiological quality; difference in seed germination between seedlots of S. lycocarpum and S. pseudoquina was observed. Alternating temperature was beneficial for seed germination of the three studied species. The standard germination test (normal seedlings), lasted for 60 days for S. granuloso-leprosum (first count at 37 days), 62 days for S. pseudoquina (first count at 33 days) and 88 days for S. lycocarpum (first count at 39 days). When the botanical criteria for seed germination (primary root emission) was used there was a decrease in the period of time for germination of 30 days for seeds of S. granuloso-leprosum and S. pseudoquina and in 58 days for seeds of S. lycocarpum.
Basis for standardization of the germination test in three Solanum L. species
Keywords: Colour; Density; Forest seeds; Physiological quality; Temperature